Introducing Shirley Braverman - Wolitzer, Hilma (New York : Farrar, Straus and Giroux, 1975)
The adventures of a sixth-grader growing up in Brooklyn during World War II
Keywords: Family life -- Fiction; Friendship -- Fiction